1996
DOI: 10.1109/20.539186
|View full text |Cite
|
Sign up to set email alerts
|

Noise and ΔM⊥ analysis of a Cr-rich Co-Cr perpendicular medium for an MR head

Abstract: The medium noise in a Cr-rich Co-Cr alloy perpendicular medium was investigated by using an MR head designed for longitudinal recording. Medium with a Cr content of 28 at.% showed a high crystalline orientation and a low write-demagnetization effect. The signal-to-noise ratio ( S N ) of the medium was higher than that of conventional Co-Cr perpendicular media for inductive heads. The advantages of the medium derive from the large inter-particle perpendicular magnetic intexaction (AML) of media, which increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…The expansion of the c-axis by the addition of a small amount of Pt may enhance the large perpendicular interaction of the Crrich medium described in ref. [3]. This reduces the demagnetization field for each particle in the medium, and contributes to the increase in the signal amplitude.…”
Section: Read-write Characterizationmentioning
confidence: 95%
See 1 more Smart Citation
“…The expansion of the c-axis by the addition of a small amount of Pt may enhance the large perpendicular interaction of the Crrich medium described in ref. [3]. This reduces the demagnetization field for each particle in the medium, and contributes to the increase in the signal amplitude.…”
Section: Read-write Characterizationmentioning
confidence: 95%
“…The authors previously reported on a perpendicular recording system using a single-layer CO-Cr medium and a merged MR head designed for longitudinal recording, and showed that a Cr-rich Co72Cr28 (at.%) medium with a thickness of 300 nm has a high signal-to-noise ratio (S/N) of 31 dB at 70 kFCI [3]. Although the value is higher than that for a conventional Co78Cr22 medium, the S/N and signal amplitude of the medium are still lower than those of a conventional longitudinal medium optimized for the MR head.…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously reported that a Cr-rich perpendicular Co 72 Cr 28 medium has an excellent signal-to-noise ratio in comparison with the conventional Co 78 Cr 22 perpendicular medium. 1 However, its output is smaller than that of the conventional medium, owing to its low M s value. Further improvement of the reproduced output is required for perpendicular recording technology to be put to practical use.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, only some papers reported systematic study on the relationship between the recording properties and macroscopic parameters in perpendicular recording media. Narrow distribution ofHc increases both output and resolution [2], exchange coupling between grains increases medium noise [3], and high Cr content reduces medium noise [4] were reported. The guiding principle for perpendicular recording media, however, may not be well established.…”
Section: Introductionmentioning
confidence: 99%